SUPERIOR SPORTS PROFILE KUBU RAYA DISTRICT - Faisal Rokhim; Eka Supriatna; Y. Touvan (Universitas Tanjungpura, 2020)
AbstractThis research is driven by the fact that the featured sports in Kubu Raya Regency had not been identified, viewed from the aspect of sports achievement, performance improvement, organization, funding, facilities and infrastructure, and trainers. This qualitative descriptive research was conducted using a survey method, of which the data were collected using questionnaires and interviews. The data of this study were collected from the Indonesian National Sports Committee (KONI) and the Branch of Featured Sports of Kubu Raya Regency. The data were analyzed descriptively based on the qualitative analysis and were validated using triangulation. Based on the findings, the featured sports of Kubu Raya Regency presented 3 sports including archery, weight lifting, and hapkido. Achievement field has been attained, the achievements obtained by athletes are good and have fulfilled the requirements. The field of achievement improvement has been accomplished; this is evidenced by the increase in achievements obtained from year to year. The organization for management performance is not working optimally. The funding sector has not been fulfilled because funds from the government are very minimal. The facilities and infrastructure sector in the branch of featured sports of Kubu Raya Regency has not been fulfilled and has not reached the quality standard.Keywords: Profile, Featured Sports